(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Accessory nipples (AN) are a common anomaly usually restricted to cosmetic concerns. However, presence of accessory nipple may suggest systemic diseases, particularly renal and urinary tract pathology. A case series links systemic diseases found during general physical examination and autopsy to AN. Complete examinations are recommended to exclude associated urinary pathology.